2005
DOI: 10.1287/isre.1050.0058
|View full text |Cite
|
Sign up to set email alerts
|

Web Personalization as a Persuasion Strategy: An Elaboration Likelihood Model Perspective

Abstract: 2005) Web Personalization as a Persuasion Strategy: An Elaboration Likelihood Model Perspective. Information Systems Research 16(3):271-291. http://dx.W ith advances in tracking and database technologies, firms are increasingly able to understand their customers and translate this understanding into products and services that appeal to them. Technologies such as collaborative filtering, data mining, and click-stream analysis enable firms to customize their offerings at the individual level. While there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
321
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(330 citation statements)
references
References 38 publications
7
321
0
2
Order By: Relevance
“…Researchers in marketing and decision-making also analyze behavioral data, but focus more on decision time, switching behavior after the choice, or total consumption volume (HĂ€ubl et al 2004;Pedersen 2000;Vijayasarathy and Jones 2001;Stolze and Nart 2004;Hostler et al 2005;Ho and Tam 2005;Tam and Ho 2005;Pathak et al 2010). A common problem with behavioral data, however, is that they are not always good indicators of users' subjective experience.…”
Section: Triangulation Of (Logged) Behavioral Datamentioning
confidence: 99%
“…Researchers in marketing and decision-making also analyze behavioral data, but focus more on decision time, switching behavior after the choice, or total consumption volume (HĂ€ubl et al 2004;Pedersen 2000;Vijayasarathy and Jones 2001;Stolze and Nart 2004;Hostler et al 2005;Ho and Tam 2005;Tam and Ho 2005;Pathak et al 2010). A common problem with behavioral data, however, is that they are not always good indicators of users' subjective experience.…”
Section: Triangulation Of (Logged) Behavioral Datamentioning
confidence: 99%
“…Tang, Jang and Morrison (2012) studied information processing by dual routes in the context of travel sites and confirmed that people are more likely to consider persuasive messages through the central route when they're relatively involved. For example, users are more likely to carefully evaluate information on the web if the content is more detailed and has more reviews by other users (Tam & Ho, 2005). However, people are more likely to go through the peripheral route if they can exert less cognitive effort by following heuristics rules (Tang et al, 2012).…”
Section: Persuasive Messagesmentioning
confidence: 99%
“…Personalized information [62] (relating content to the user and his activities) is included and prioritized in all relevant pages to increase persuasion [63] and facilitate participation for both novice and expert users [64]. For example, when browsing application or component models, system recommendations for models that might be of interest to the user are displayed topmost.…”
Section: Prioritization Of Personalized Informationmentioning
confidence: 99%